Health Risk Assessment for Transport Corridors in Delhi through Vehicular Air Polluting Mapping (International Journal of Built Environment and Sustainability, 2016)
Vehicles are recognized as one of the major sources of air pollution. Delhi having  a very large number of vehicles produces a lot of air pollution. There is an utter need to ascertain the concentration of the pollutants and their impact on the health of the people of the concerned region. This paper makes an attempt towards such an examination. The method employed here is based on Epidemiology. The assessment of health risks due to increased levels of various pollutants on people represented in this paper is based on the spreadsheet model, Risk of Mortality/Morbidity due to Air Pollution (Ri–MAP). This paper presents the findings of the study that evaluates the Impact of increasing air pollution on human health, especially vehicular pollution, in the monitored region, i.e., National Capital Territory of Delhi (NCT Delhi) during the year 2015 by choosing fifteen study sites from different parts of the capital city. The findings are in terms of  excess number of cases of cardiovascular and respiratory mortality, and cardiovascular and respiratory morbidity for all fifteen transport corridors. Among others, Noida link road recorded highest excess number of cases of cardiovascular mortality and morbidity and respiratory Morbidity. In case of respiratory mortality, Wazirabad road recorded maximum excess number of cases. With respect to least excess number of cases, it was Connaught Place (Outer circle). The excess number of cases are directly proportional to the population density of the respective region. Also, the regions showing smaller excess number of cases are the planned, less crowded and posh regions of the national capital territory of Delhi.